Studi Literatur Gambaran Gejala Klinis dan Patologi Anatomi African Swine Fever pada Babi - Brito Araujo; Tri Utami; Tarsisius C Tophianong (Jurnal Veteriner Nusantara, 2023)
African Swine Fever (ASF) is an infectious disease in pigs caused by a double-stranded DNA virus from the Asfarviridae family. This disease is generally characterized by bleeding in the ears, back and legs. This virus causes death and has a large economic impact, however ASF is not a zoonotic disease so it does not have an impact on human health. The results of necropsy in dead pigs showed abnormalities in the organs such as erythrema of the skin, swollen and hyperemic pulmonary edema, the spleen turned black, the liver was swollen, there was fluid in the pericardium and ptechie or haemorrhages were often found in the heart, kidneys. Control and prevention for ASF until now there is no effective treatment and vaccine. Control and prevention efforts are to eradicate pigs infected by the ASF virus and control biosafety and biosecurity as the most effective measures to prevent and control ASF virus. African swine fever has no pathognomonic symptoms, so that the clinical symptoms are similar to other hemorrhagic diseases such as Classical Swine Fever, salmonellosis or erysipelas so it is necessary to carry out pathological anatomical examinations. Changes in anatomical pathology ASF disease macroscopically.